3D printed GelMA/carboxymethyl chitosan composite scaffolds for vasculogenesis. Issue 7 (3rd May 2023) - Wang, Lijing; Cao, Yanyan; Shen, Zhizhong; Li, Meng; Zhang, Wendong; Liu, Yu; Zhang, Yating; Duan, Jiahui; Ma, Zhuwei; Sang, Shengbo
Abstract: The establishment of vascularization is the basic prerequisite for the survival and functionalization of three-dimensional (3 D) tissue-engineered constructs. The application of hydrogel to tissue regeneration has promoted the research and development of regenerative medicine. In this study, we fabricated the composite scaffold composed of gelatin methacryloyl (GelMA) and carboxymethyl chitosan (CMCS) and proved the potential of the scaffold to promote angiogenesis. To characterize the physical properties of the composite scaffold, the mechanical strength, swelling ratio and internal microstructure were tested. The biocompatibility of the GelMA/CMCS scaffold was evaluated by live/dead test and CCK-8. To evaluate the cell distribution, CD31 expression and endothelial differentiation of seeded rat bone marrow mesenchymal stem cells (BMSCs) on the scaffolds, the cytoskeletal staining, immunofluorescence staining and real-time PCR were performed. The composite GelMA/CMCS scaffolds seeded with BMSCs showed excellent mechanical properties, CD31 expression and vasculogenesis genes expression, compared with the pure GelMA scaffold. Furthermore, the activity of BMSCs in 3 D printed GelMA/CMCS scaffolds proved the feasibility of the bioprinting of cells-laden GelMA/CMCS composite scaffolds. In conclusion, our study demonstrated the potential of GelMA/CMCS composite scaffolds for vascular tissue engineering. Graphical Abstract: UF0001